Actions Speak Louder than Words: How Figurative Language and Gesturing in Entrepreneurial Pitches Influences Investment Judgments - Clarke, Jean S.; Cornelissen, Joep P.; Healey, Mark P. (Academy of Management Journal, 2019)
A key challenge for entrepreneurs is to convince investors of their business ideas via a pitch. While scholars have started to explore how entrepreneurs convey their passion and preparedness in a pitch, they have overlooked the possible variation that exists in entrepreneurs’ verbal and nonverbal expressions. We build on research in cognitive science and entrepreneurship to examine the nature and influence of specific forms of speech and gesturing used by entrepreneurs when pitching. In an initial qualitative field study we identify distinct pitching strategies entrepreneurs use, involving different combinations of verbal tactics (i.e., using literal and figurative language to frame a venture) and gesture (i.e., using different types of hand gestures to emphasize parts of their pitch and convey product and venture ideas). In a subsequent experimental study, we examine the impact of these strategies on investors’ propensity to invest. We find that, although variation in the type of language used by an entrepreneur has limited effects, using gestures to depict and symbolize business ideas has strong positive effects. Our findings indicate that the skilled use of gestures by entrepreneurs helps potential investors imagine aspects of a new venture for themselves, thereby enhancing perception of its investment potential.